Model of trainee recruitment for f&bservice at KeP Restaurant of The K. Resort Ubud Bali during new normal - Arimasputri, Ida Ayu Novira Megarani; Damayanti, Ida Ayu Kade Werdika; Susyarini, Ni Putu Wiwiek Ary; Kanca, I Nyoman; Budiarta, Putu (YAYASAN MITRA PERSADA NUSANTARA, 2023)
The purpose of this study was to determine the trainee recruitment model used by HRD of the company. This research was analyzed using descriptive analysis technique with a qualitative approach. The data collected in this study was conducted through direct observation and in-depth interviews with informants. This study determines the informants intentionally based on the data collection needs of this study. Informants in this study were Senior Admin HRD and Supervisor. The results of the research show that the hotel does not yet have a recruitment model that becomes a standard procedure and assessment. The recruitment model as a result of this research comes in the form of a rubric that can be applied by HRD in the next trainee recruitment during the new normal period.